(3z+7)(2+-1z)=0

Simple and best practice solution for (3z+7)(2+-1z)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3z+7)(2+-1z)=0 equation:


Simplifying
(3z + 7)(2 + -1z) = 0

Reorder the terms:
(7 + 3z)(2 + -1z) = 0

Multiply (7 + 3z) * (2 + -1z)
(7(2 + -1z) + 3z * (2 + -1z)) = 0
((2 * 7 + -1z * 7) + 3z * (2 + -1z)) = 0
((14 + -7z) + 3z * (2 + -1z)) = 0
(14 + -7z + (2 * 3z + -1z * 3z)) = 0
(14 + -7z + (6z + -3z2)) = 0

Combine like terms: -7z + 6z = -1z
(14 + -1z + -3z2) = 0

Solving
14 + -1z + -3z2 = 0

Solving for variable 'z'.

Factor a trinomial.
(2 + -1z)(7 + 3z) = 0

Subproblem 1

Set the factor '(2 + -1z)' equal to zero and attempt to solve: Simplifying 2 + -1z = 0 Solving 2 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1z = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1z = 0 + -2 -1z = 0 + -2 Combine like terms: 0 + -2 = -2 -1z = -2 Divide each side by '-1'. z = 2 Simplifying z = 2

Subproblem 2

Set the factor '(7 + 3z)' equal to zero and attempt to solve: Simplifying 7 + 3z = 0 Solving 7 + 3z = 0 Move all terms containing z to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3z = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 3z = 0 + -7 3z = 0 + -7 Combine like terms: 0 + -7 = -7 3z = -7 Divide each side by '3'. z = -2.333333333 Simplifying z = -2.333333333

Solution

z = {2, -2.333333333}

See similar equations:

| 1/2(4r^2-2r)=6 | | 8(z+3)+7(z+2)=5z+6(z+1) | | -5(x+4)-8=-28 | | (x+y)(x-y)(x^2-Y^2)= | | -3+v=-8 | | 8n-28= | | 72+4x=180 | | 4w=-52 | | 3x-5y=k | | TC=3Q+3Q^3 | | 12-6w= | | 3x+9z=-1 | | (9x)^0(7y)^2/((9x)^2(y3)^5 | | 8=u-1 | | 59=5v+14 | | n+7+n+2n-12=90cm | | X+7y=-60 | | m-10=-40 | | 6=9a | | 6-(4n-1)=2-5n | | 4=10y | | z-2(z+1)=3z-(20-5z) | | 3x+6=6-x | | p^2-12p+45=0 | | x^2+2x^2-900=0 | | 4/25•2/5= | | 4(2x+5)=-17+5 | | 1 = c2 | | q+7=9 | | 7r=60-5R | | 3 = d2 | | 7-4(4-(3y-7))=0 |

Equations solver categories